Ecocriticism - Garrard, Greg (New critical idiom, 2023)
"Ecocriticism explores the ways in which we imagine and portray the relationship between humans and the environment across many areas of cultural production, including Romantic poetry, wildlife documentaries, climate models, the Hollywood blockbuster The Day After Tomorrow, and novels by Margaret Atwood, Kim Scott, Barbara Kingsolver and Octavia Butler. Greg Garrard's animated and accessible volume responds to the diversity of the field today and explores its key concepts, including: - pollution - pastoral - wilderness - apocalypse - animals - Indigeneity - the Earth. Thoroughly revised to reflect the breadth and diversity of twenty-first-century environmental writing and criticism, this edition addresses climate change and justice throughout, and features a new chapter on Indigeneity. It also presents a glossary of terms and suggestions for further reading. Concise, clear, and authoritative, Ecocriticism offers the ideal introduction to this crucial subject for students of literary and cultural studies"-- Provided by publisher.